LEXICAL AND GRAMMATICAL ERRORS IN SPEECH PRODUCTION: A DESCRIPTIVE QUALITATIVE STUDY OF HIGH SCHOOL STUDENTS IN BANDUNG - Eri Subekti (Institut Pendidikan Indonesia Garut, 2018)
This study is about lexical and grammatical errors in students’ speech production of speaking performance. The aims of the study are to find out the kinds of errors in the speaking performance and the error which is most frequently occurred. The participants were 36 high school students in the level of beginner. In lexical errors, the classifications are divided into two kinds, they are: 1) Lexical errors constitute collocations, idioms, content and functional words and errors of derivational morphology; and 2) Lexical errors constitute unintentional use of L1 lexemes. The Grammatical Errors are divided into two classifications of Syntactic Errors and Morphological Errors. Based on the oral distributions, the most frequent error occurred is morphological error regarding the omitted and misused ‘be’.